Transformational Leadership, Reward System, and Organizational Climate to Employee Commitment Office Regional Revenue Agency Labuhanbatu Regency - Imas Riana Sirait; Junita Lubis; Abd. Halim (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of transformational leadership, reward system and organizational climate on the commitment of employees of the Regional Revenue Agency Office of Labuhanbatu Regency. This study uses quantitative methods with analytical techniques such as classical assumption test, multiple linear regression, hypothesis testing, and the coefficient of determination.IBM SPSS Softwareused by researchers to facilitate the process of data processing. The research data was obtained through interviews and distributing questionnaires given to the related employees. The results of this study indicate that all independent variables are partially dependent on the dependent variable, this is evident from the results of the t test which can be described as follows, the value oftcount transformational leadership variable (X1) 7,18 > ttable1.66 with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the transformational leadership variable has a positive and significant effect on employee commitment. Marktcount reward system variable (X2) 6.70 > ttable1.66 with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the group cooperation variable has a positive and significant effect on employee commitment. Marktcount organizational climate variable (X3) 11.17 > ttable1.66 with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the organizational climate variable has a positive and significant effect on employee commitment. Simultaneously, the variables of transformational leadership, reward system, and organizational climate have a positive and significant influence on employee commitment. This means that the hypothesis in this study is accepted, as evidenced by the value of Fcount > Ftable (86.02>2.71).